Electronic Word-Of-Mouth dalam Pembelian Produk Kecantikan - Aura Fonda Firdausa; Livina Livina; Istijanto Istijanto; Krishnamurti Murniadi (Universitas Prasetiya Mulya, 2022)
The purpose of this study is to examine whether the factors of e-WOM involvement (consumer opinions both positively and negatively towards a product or brand that are disseminated via the internet) can influence the intention to purchase skincare products on Instagram in Indonesia, through the Elaboration Likelihood Model (ELM) theory. and Theory of Reasoned Action (TRA). Data analysis was carried out using AMOS Structural Equation Modeling (SEM) with 360 respondent data through online questionnaires and using a non-probability sampling technique, namely judgmental sampling. This study provides findings, namely: (1) the quality of information and the quality of brand Instagram accounts have no effect on e-WOM involvement, (2) information credibility, social support, innovative behavior, and attitudes towards e-WOM have a significant effect on e-WOM involvement, (3) attitudes towards e-WOM have a significant effect on purchase intention, and (4) e-WOM involvement has a significant effect on purchase intention.